2013
DOI: 10.1152/ajprenal.00004.2013
|View full text |Cite
|
Sign up to set email alerts
|

Increased susceptibility of db/db mice to rosiglitazone-induced plasma volume expansion: role of dysregulation of renal water transporters

Abstract: T. Increased susceptibility of db/db mice to rosiglitazone-induced plasma volume expansion: role of dysregulation of renal water transporters. Am J Physiol Renal Physiol 305: F1491-F1497, 2013. First published September 4, 2013 doi:10.1152/ajprenal.00004.2013, which are synthetic peroxisome proliferator-activated receptor subtype-␥ (PPAR␥), agonists are highly effective for treatment of type 2 diabetes. However, the side effect of fluid retention has significantly limited their application. Most of the previ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
13
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…First, this effect might be related to the glycemic control by Rosi. As shown by previous reports, Rosi markedly decreased the blood glucose level in db/db mice [23, 3335]. Our result also showed that a moderate hyperglycemia in this obese-diabetic db/db mouse strain was almost normalized following 1-week Rosi therapy.…”
Section: Discussionsupporting
confidence: 90%
“…First, this effect might be related to the glycemic control by Rosi. As shown by previous reports, Rosi markedly decreased the blood glucose level in db/db mice [23, 3335]. Our result also showed that a moderate hyperglycemia in this obese-diabetic db/db mouse strain was almost normalized following 1-week Rosi therapy.…”
Section: Discussionsupporting
confidence: 90%
“…Skeletal muscle myosin enzymatic activity is required for pulmonary myofibroblast contractility (Walker et al ., ; Rice and Leinwand, ), and increased intracellular calcium has a notable effect on the activity of the adult fast myosin heavy chain promoters (Allen and Leinwand, ). Additionally, low serum potassium promotes the development of diabetes and increases the risk of lethal ventricular arrhythmias in patients with ischaemic heart disease, heart failure and left ventricular hypertrophy (He and MacGregor, ), and increased urinary Na + excretion and urine volume are exhibited in natriuresis (Zhou et al ., ). Herein, we feel that further study is necessary to assess the effects of GNP exposure on the physiological condition (Park et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…This includes weight gain, fluid retention, bone mineral density reduction, and excess myocardial infarction [24]. The fluid retention induced by TZDs has also been proven to significantly increase urine volume and excretion of sodium [25]. Because of this, there is some controversy surrounding the safety of longterm TZD usage to treat diabetes.…”
Section: Discussionmentioning
confidence: 99%
“…This may signify a stage shift, by pioglitazone treatment, from developing cancer. PPARγ agonism has also been shown to increase the antitumor effects of histone deacetylase inhibitors in multiple myeloma cells [25].…”
Section: Discussionmentioning
confidence: 99%